Lithium Toxicity in an Elderly Women within Normal Therapeutic Range : A Case Report (Chattagram Maa-O-Shishu Hospital Medical College Journal, 2015)
Toxic effects of lithium are usually related to high serum levels. However, several cases of significant toxicity have occurred in patients whose serum levels fell within the normal therapeutic range. Such cases are rare, but individual variations may occur and clinical judgment rather than serum levels must determine the management. A 67 years old female with bipolar disorder on lithium was admitted with an acute confusional state, tremor, restlessness, increased nausea, slurred speech, polyuria and diarrhoea. Lithium level found to be 0.6 mmol/L that is in normal range. Neurotoxicity could be suspected at serum lithium levels which are considered therapeutic in young adults.Chatt Maa Shi Hosp Med Coll J; Vol.14 (2); Jul 2015; Page 78-79